KONSEP ETNOSAINS PADA PROSESI BARODAK ADAT PERNIKAHAN SUMBAWA DALAM PEMBELAJARAN IPA (Wujud Benda Di Alam Sekitar) - Idam Ragil Widianto Atmojo; Fini Ummul Wafa (Jurnal Penelitian Pendidikan IPA, 2022)
This research can improve science learning, one of which is by integrating science learning using values in local culture. This study aims to describe the concept of ethnoscience in the barodak procession at Sumbawa traditional weddings with science learning in elementary schools. In the traditional Berodak procession at a wedding in Sumbawa Regency, which uses the form of objects that exist in the nature around us. The writing method used in this article is a qualitative research type. This research is in the form of activities, ideas and mindsets that are reflected in barodak culture. Sources of data were obtained from the indigenous people of Sumbawa who were used as informants and literature studies. The technique used is an interview technique by asking several questions related to the barodak procession. By utilizing the form of objects from the natural around us. So that students can understand the shape of objects from the natural surroundings that are in Sumbawa so many and rich in benefits. Based on the results of the discussion of science learning, it will be more effective if it is related to the culture in the surrounding environment so that students can better understand learning.